On Self-Esteem as a Predictor for a Future Profession in the Field of Communication - Popa, Daniela (Journal of Danubian Studies and Research, 2023)
Even if the priority of educational training is intellectual development, its purpose is also aimed at training people who have skills for their future profession. Many articles and research have focused on students and their learning environment studying what helps them or not to access the professions for which they have been trained. One of the most important factors contributing to school success is self-esteem because self-esteem interferes with good academic learning. The development of self-esteem is shaped by life-long learning experiences, the dynamic process of individual perspective and the qualities of the self. However, the culture and social context have proven to be factors that interfere with self-esteem interpretations because when society’s expectations do not match with their actual performance, the self-esteem can be affected.